The Effect of Price and Product Quality on Online Purchasing Decisions: Empirical Study in Lazada - Ansir Launtu (Jurnal Manajemen Bisnis, 2021)
The purpose of this study is to investigate the relationship between price, product quality, and online purchasing decisions in E-Commerce. The survey method is used to consider that this method is quite economical, fast, guarantees the respondent's flexibility to answer and gather the necessary facts, and guarantees the confidentiality of the respondent's identity to provide information or answers. The data collection method in this study used a questionnaire involving 100 respondents which use Lazada. The results shown in this study confirm that prices and products have a positive and significant effect on purchasing decisions.